Strategic Communication and Electoral Outcomes in Nigeria: Examining the Influence of New Media Campaigns on Voter Behaviour - Okunade Joshua Kayode; Abdullahi Aliyu Maiwada; Mohammed Jibril Nasir; Joseph Ifeoluwa Joy (Polit Journal Scientific Journal of Politics, 2026)
This study explores the role of strategic communication in Nigerian political campaigns, emphasizing the impact of new media and messaging strategies on electoral outcomes. This research aims to fill this gap by providing a comprehensive analysis of how strategic communication, facilitated by new media, influences political campaigns and electoral results in Nigeria. Two pertinent theories deployed for the study are the Agenda-Setting Theory and the Uses and Gratifications Theory. A questionnaire survey was administered to a diverse sample of Nigerian voters, yielding insights into demographic characteristics, primary sources of political information, and perceptions of strategic communication effectiveness. This study underscores the critical role of strategic communication in Nigerian political campaigns, particularly through digital platforms. The findings reveal that a well-educated and economically diverse electorate, predominantly middle-aged and self-employed, engages actively in political discourse. With social media emerging as the primary source of political information, platforms such as Instagram and Twitter have become pivotal in mobilizing and influencing voters, especially young adults. The study highlights that message consistency and clarity significantly impact voter behavior, reinforcing the effectiveness of emotional and issue-based messaging. It is recommended that political organizations and media houses should conduct digital literacy campaigns to help voters critically assess political information just as an increased interactivity on social media platforms can enhance direct engagement between political actors and the electorate. Policymakers should implement guidelines to curb misinformation and promote fact-based political communication. Social media platforms should collaborate with electoral bodies to prevent the spread of misleading political content.